2021
DOI: 10.1097/cm9.0000000000001625
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and years of life lost of colorectal cancer in China, 2005–2020: findings from the national mortality surveillance system

Abstract: Background: Colorectal cancer (CRC) is the fourth cause of cancer death in China. We aimed to provide national and subnational estimates and changes of CRC premature mortality burden during 2005–2020. Methods: Data from multi-source on the basis of the national surveillance mortality system were used to estimate mortality and years of life lost (YLL) of CRC in the Chinese population during 2005–2020. Estimates were generated and compared for 31 provincial-level administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“… 1 The burden of CRC is also crucial in China, ranking as the fourth leading cause of cancer-related deaths. 3 The interest in early-onset CRC (EOCRC) has been increasing, which is defined as CRC that occurs under the age of 50 years. A previous study conducted in nine high-income countries found that the incidence of EOCRC was increasing.…”
Section: Introductionmentioning
confidence: 99%
“… 1 The burden of CRC is also crucial in China, ranking as the fourth leading cause of cancer-related deaths. 3 The interest in early-onset CRC (EOCRC) has been increasing, which is defined as CRC that occurs under the age of 50 years. A previous study conducted in nine high-income countries found that the incidence of EOCRC was increasing.…”
Section: Introductionmentioning
confidence: 99%
“…According to a report of the cancer survey, colorectal cancer ranks in the top three in new cases and deaths in both men and women, making it one of the most life-threatening cancers among Chinese patients [ 1 , 2 ]. The progression of colorectal adenomas to cancer may take up to 10 years, and the incidence increases with age [ 3 6 ]. Moreover, the risk of mortality from colorectal cancer has been reported to decrease by 53% in patients who underwent endoscopic adenoma resection [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China, estimated colorectal cancer (CRC) deaths increased from 111.41 thousand in 2005 to 178.02 thousand in 2020; age‐standardized mortality rate decreased from 10.01 per 100,000 in 2005 to 9.68 per 100,000 in 2020. 1 Vitamin D level is inversely associated with CRC development, influences prognosis, and survival rate. 2 In CRC patients undergoing surgery, vitamin D influences the risk of infectious complications.…”
Section: Introductionmentioning
confidence: 99%